Potential for Musculoskeletal Disorders of Buruh Gendong in Legi Market - Suparti, Erni; Wahyudi, Adhie Tri; Zendrato, Rosleini Ria Putri; Perkasa, Kevin Fajar (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2023)
The people in Surakarta are still going to the traditional market. Even though the modern markets are starting to appear such as supermarkets, hypermarts, or malls. One of the traditional markets that is classified as class 1 in the city of Solo is Legi Market. Legi Market which is located at Jalan S. Parman No. 19 Setabelan, Banjarsari is the main market in the city of Solo. “Buruh Gendong” is a person who help others to carry the goods. “Buruh Gendong” have an important role in Legi Market. They bring goods from outside to be brought inside market or they bring goods from buyers to be taken outside to the parking area. There are around 200 “Buruh Gendong” in Legi Market, with an average age of over 40 years old. The weight of the load is aproximately 30 kg to 100 kg. The distance from inside to outside is about 50 meters. Almost Buruh Gendong do not aware with the impact of their duty to the skeletal system,called Musculoskeletal Disorders (MsDs). Mapping the potential for MSDs is very helpful for the government for reducing the incidence of skeletal muscle injury. This study will discuss how to overcome MsDs. Keywords: Musculoskeletal Disorders, Buruh Gendong of Legi Traditional Market, Recommended Weight Limit